Developing Secure Messaging Software using Post-Quantum Cryptography - Nguyen, Tat-Thang; Luc, Nhu-Quynh; Dao, Thanh Toan (Engineering, Technology & Applied Science Research, 2023)
In this paper, a technique to develop a secure messaging service utilizing a new post-quantum cryptosystem, termed CryptoMess, is proposed. Commutative Supersingular Isogeny Diffie-Hellman (CSIDH) is utilized to secure key exchange paired with the AES algorithm to protect message content in communication. At the same time, the Rainbow post-quantum digital signature technology is incorporated to assure the integrity and authenticity of communications between the sender and the recipient. As a consequence, the messaging program is able to exchange messages between users, assuring safety, security, integrity, and authenticity. The performance of the program has a transmitting rate of approximately 0.26 s and a receiving rate of approximately 0.22 s. The message signing time is approximately 0.027 s, the message verification speed is approximately 0.22 s, and the key exchange time is approximately 0.0017s.